2000
DOI: 10.1007/s100520000483
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive leptoproduction of $\rho^0$ mesons from hydrogen at intermediate virtual photon energies

Abstract: Abstract. Measurements of the cross section for exclusive virtual-photoproduction of ρ 0 mesons from hydrogen are reported. The data were collected by the HERMES experiment using 27.5 GeV positrons incident on a hydrogen gas target in the HERA storage ring. The invariant mass W of the photon-nucleon system ranges from 4.0 to 6.0 GeV, while the negative squared four-momentum Q 2 of the virtual photon varies from 0.7 to 5.0 GeV 2 . The present data together with most of the previous data in the intermediate W -d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
156
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(176 citation statements)
references
References 27 publications
18
156
2
Order By: Relevance
“…In 2005 the HERMES collaboration published first evidence for azimuthal singlespin asymmetries (SSA) in the semi-inclusive production of charged pions on a transversely polarised target [1]. Significant signals for both the Collins and Sivers mechanisms were observed in data recorded during the 2002-2003 running period of the HERMES experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005 the HERMES collaboration published first evidence for azimuthal singlespin asymmetries (SSA) in the semi-inclusive production of charged pions on a transversely polarised target [1]. Significant signals for both the Collins and Sivers mechanisms were observed in data recorded during the 2002-2003 running period of the HERMES experiment.…”
mentioning
confidence: 99%
“…Recent studies showed that the terms for sin φ S and sin (2φ − φ S ) have to be added in the two-dimensional least-squares fit for the asymmetry (the kinematic factors A ( y , R ) and B ( y ) are defined in [1]):…”
mentioning
confidence: 99%
“…The simplest process to measure is deeply virtual Compton Scattering (DVCS), where a photon is produced by a parton from the nucleon [6,7,8,9,10]. It is also possible to interpret measurements of produced mesons in the GPD framework, e.g.…”
Section: Exclusive Physicsmentioning
confidence: 99%
“…This event selection technique allows a certain amount of background into the data sample, mostly from events involving a resonant state of the target nucleon. The collaboration has also published measurements from an kinematically completely recostructed data sample [15] that was taken with additional experimental equipment-the beam helicity asymmetry measured using an exclusive event selection technique is shown in figure 4. Unfortunately, there is only a single beam charge available for this additional dataset, so it is not possible to distinguish between the contributions from the interference and |DVCS| 2 terms to the asymmetry.…”
Section: Exclusive Physicsmentioning
confidence: 99%
“…In general, the differential and total cross sections for ρ 0 -meson production by virtual photons are reasonably well described in the GPD-based approach of Refs. [15,16], not only at the high energies of the HERA collider experiments [20][21][22][23][24], but also at intermediate energies covered by the fixed-target experiments E665 [25] and HERMES [26].…”
Section: Introductionmentioning
confidence: 99%